First-principles studies of structural, elastic, electronic, optical and lattice dynamical properties of XSnP2 (X = Zn, Cd and Hg) compounds. (November 2019) - Zhong, Yuhan; Mei, Huayue; He, Dafang; Du, Xue; Cheng, Nanpu
Abstract: The structural, elastic, electronic, optical, lattice dynamical and thermodynamic properties of X SnP2 ( X = Zn, Cd and Hg) compounds with chalcopyrite structure were studied using density functional theory. Including the newly predicted HgSnP2, X SnP2 compounds are thermodynamically, mechanically and dynamically stable. The calculated elastic constant, bulk modulus, shear modulus, Young's modulus and Poisson's ratio reveal that X SnP2 compounds are elastic anisotropic: ZnSnP2 is brittle, but CdSnP2 and HgSnP2 are ductile. The X SnP2 compounds are direct-gap semiconductors with band gaps of 2.062, 1.424 and 0.543 eV, respectively. All X SnP2 compounds have strong absorptions and high conductivities in the ultraviolet region. Especially, HgSnP2 has the greatest absorption coefficient and conductivity in the visible region, indicating that it has the strongest visible-light absorption capacity and the best photovoltaic activity. For X SnP2 compounds, the D 2 d group has five irreducible representations: A1, A2, B1, B2 and E. Modes A1 and A2 only involve displacements of P atoms, but the other three modes involve vibrations of X, Sn and P atoms. Based on the calculated phonon spectra of X SnP2, their thermodynamic properties were also analyzed in detail. The current work deepened the understanding of crystal structures and physical properties of X SnP2 compounds, and will aid in their potential application. Highlights: X SnP2 ( X = Zn, Cd and Hg) compounds' crystal structures and physical properties were studied. HgSnP2 is proved to exist theoretically. HgSnP2 has the highest absorption coefficient and conductivity in the visible region. The A1 and A2 modes only involve displacements of P atoms. Modes B1, B2 and E involve vibrations of X, Sn and P atoms.